EFFECT OF RELATIONSHIP MARKETING, STORE IMAGE, AND COMPLETENESS OF PRODUCTS TO CUSTOMER LOYALTY THROUGH TRUST AS VARIABLE INTERVENING (STUDY ON PAKNING JAYA TRADE BUSINESS) - Kevin Adrian; Astri Ayu Purwati; Sarli Rahman; Mazzlida Mat Deli; Mujtaba M. Momin (International Conference on Business Management and Accounting, 2022)
The level of competition in the business world is already considered very tight in Indonesia because every business tries to attract market share in order to retain consumers and attract new consumers. Therefore, it is necessary to carry out various efforts through market strategies in order to win the competition and ultimately achieve business objectives. One aspect of taking part in a change is the public's demand for loyalty. This study aims to determine and analyze the effect of Relationship Marketing, Store Image, and product completeness on consumer loyalty through Trust as a variable intervening in the Pakning Jaya trading business. The number of respondents used in this research is 100 respondents who shop at Pakning Jaya trading business. The research analysis technique used in this research is Accidental Sampling analysis using descriptive analysis and multiple linear regression with the help of PLS software. From the tests that have been done, it can be seen that Relationship Marketing, Store Image, and product completeness have affected customer loyalty to consumers of Pakning Jaya's trading business.